Influence of soil density on gas permeability and water retention in soils amended with in-house produced biochar - Garg, Ankit; Huang, He; Cai, Weiling; Reddy, Narala Gangadhara; Chen, Peinan; Han, Yifan; Kamchoom, Viroon; Gaurav, Shubham; Zhu, Hong Hu (My University, 2021)
Biochar has been used as an environment-friendly enhancer to improve the hydraulic properties (e.g. suction and water retention) of soil. However, variations in densities alter the properties of the soil–biochar mix. Such density variations are observed in agriculture (loosely compacted) and engineering (densely compacted) applications. The influence of biochar amendment on gas permeability of soil has been barely investigated, especially for soil with different densities. The major objective of this study is to investigate the water retention capacity, and gas permeability of biochar-amended soil (BAS) with different biochar contents under varying degree of compaction (DOC) conditions. In-house produced novel biochar was mixed with the soil at different amendment rates (i.e. biochar contents of 0%, 5% and 10%). All BAS samples were compacted at three DOCs (65%, 80% and 95%) in polyvinyl chloride (PVC) tubes. Each soil column was subjected to drying–wetting cycles, during which soil suction, water content, and gas permeability were measured. A simplified theoretical framework for estimating the void ratio of BAS was proposed. The experimental results reveal that the addition of biochar significantly decreased gas permeability kg as compared with that of bare soil (BS). However, the addition of 5% biochar is found to be optimum in decreasing kg with an increase of DOC (i.e. kg,65% > kg,80% > kg,95%) at a relatively low suction range (< 200 kPa) because both biochar and compaction treatment reduce the connected pores.
Keywords: Biochar; Degree of compaction (DOC); Gas permeability; Soil water retention; Wetting–drying cycle